Diversity and composition of beetles of Bernardo O’Higgins National Park (region of Magallanes, Chile) - Muñoz-Escobar, Christian; Jerez, Viviane (BOSQUE, 2017)
Bernardo O’Higgins National Park (BONP) is the largest protected area in Chile and southern hemisphere. With over 3.5 million hectares, it has a complex continental and archipelagic topography with a mosaic of evergreen forests, coastal scrub and peatlands. Given the future of the Chilean environmental legislation, all protected areas will be re-evaluated according to scientific parameters. Therefore, and considering that insects are currently recognized by the Chilean law, we aim at providing information on the spatial distribution of beetles using pitfall traps in 20 sites associated with the park. We evaluate the effect of vegetation and type of environment (insular, continental) on taxonomic composition, richness, abundance and diversity of beetles. A total of 15 families, 33 genera and 38 species were recorded. Many of these represent monotypic groups. The most diverse families were Carabidae, Staphylinidae and Curculionidae. No significant effect of vegetation and type of environment on any community measurement was observed since the vegetation and sectors analyzed are part of a larger biogeographic unit. Additionally, we determined 11 species to the park, which are significantly associated among them. We discuss the importance of this kind of information to make biogeographical approaches.